Infrastructure planning emergency levels of service for the Wellington region, Aotearoa New Zealand – A preliminary framework. (1st April 2022) - Mowll, R.; Becker, J.S.; Wotherspoon, L.; Stewart, C.; Johnston, D.; Neeley, D.; Rovins, J.; Ripley, S.
Abstract: Elements of a potential emergency response to a major hazard event can be identified early in the response planning process. Having goals for emergency provision of services, particularly infrastructure, would provide clear planning goals and actions for emergency responders. Agreed goals would also help residents more fully understand the likely nature of the service provisions following a major hazard event, allowing them to plan for events and resulting infrastructure outages. This paper proposes a set of 'planning emergency levels of service' based in literature and developed by practitioners that could be used to understand post-event planning and actions, across the critical infrastructure sectors. The resulting framework contains proposed planning emergency levels of service for the energy, telecommunications, transport, and water sectors. With potential local adjustment, this framework may be more widely applicable for other high-income regions. Limitations of the framework include that it has been developed based on literature and emergency management professionals' opinions and requires more research to ascertain its operational applicability.